Team Citizenship Pressure: How Does It Relate to OCB and Citizenship Fatigue. (April 2023) - Eliyahu, Noy; Somech, Anit
The aim of this research is to shed light on the phenomenon of citizenship pressure as a team-level construct. Building on the conservation of resources theory, the study used a moderated-mediation model to explore whether team organizational citizenship behavior (OCB) mediates the relationship between team citizenship pressure and team citizenship fatigue and whether this mediation is moderated by perceived supervisor support. Results from a study of 91 professional teams in the educational system indicate that team citizenship pressure had a significant and positive relationship with team OCB, as well as with team citizenship fatigue. The results also support the overall moderated-mediation model, but contrary to the hypothesized pattern of interaction, we found that team citizenship pressure was significantly and positively correlated with OCB when perceived supervisor support was low, but not when it was high. Limitations and implications for future research are discussed.